2010
DOI: 10.1039/b922031c
|View full text |Cite
|
Sign up to set email alerts
|

Steric control of the reduction of carbodiimides by samarium(ii) and the synthesis of very crowded samarium(iii) complexes

Abstract: Reduction of N,N'-di(2,6-diisopropylphenyl)carbodiimide (DippNCNDipp) by [SmL(2)(thf)(2)] (1) (L = N,N'-bis(2,6-diisopropylphenyl)formamidinate, DippNC(H)NDipp) in PhMe gave [Sm(L)(3)] (2) in good yield. An analogous reaction of 1 with N,N'-dimesitylcarbodiimide (MesNCNMes) gave [SmL(2)(MesNC(H)NMes)] (3). In contrast, reduction of N,N'-dicyclohexylcarbodiimide (CyNCNCy) by 1 in PhMe gave mixture of products from which [SmL(2)(CyNC(CH(2)Ph)NCy)] (4) and [SmL(2)(CyNC(H)NCy)] (5) were isolated by fractional crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…or Tianjiao (Baotou, People's Republic of China) as ingots, powders, or rods and stored under nitrogen in a glovebox. [Sm(DippForm) 2 (thf) 2 ] (1), 9 [La(DippForm) 2 F(thf)], 7 tetraphenylcyclopentadiene, 26 [Li(DippForm)(thf) 3 ], 27 Dipp-FormH, 28 and Hg(2-BrC 6 F 4 ) 2 29 were prepared by literature methods. Synthesis of [Sm(DippForm) 2 Cl(thf)] (2).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…or Tianjiao (Baotou, People's Republic of China) as ingots, powders, or rods and stored under nitrogen in a glovebox. [Sm(DippForm) 2 (thf) 2 ] (1), 9 [La(DippForm) 2 F(thf)], 7 tetraphenylcyclopentadiene, 26 [Li(DippForm)(thf) 3 ], 27 Dipp-FormH, 28 and Hg(2-BrC 6 F 4 ) 2 29 were prepared by literature methods. Synthesis of [Sm(DippForm) 2 Cl(thf)] (2).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…12 Oxidation studies of rare‐earth metal formamidinate complexes have so far only involved reactions of divalent Yb11c and Sm complexes 12. 13 Currently there is only one example of a cerium formamidinate complex, namely the trivalent [Ce(DippForm) 2 F(thf)] (DippForm= N , N ′‐bis(2,6‐diisopropylphenyl)formamidinate), and its possible oxidation was not examined 11b. Thus, trivalent and tetravalent cerium formamidinate chemistry is still an unexplored area.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, Hill et al have recently shown that the Mg-mediated reaction between alkynes and isocyanates forms bis(imidazolidine-2,4-diones). 5 Carbodiimide insertion into M−C bonds of terminal acetylides to afford the corresponding propargylamidinate has been documented for Li, 6 K, 7 Ca, 8 Y, 9 Sm, 10 Yb, 9a Lu, 9a and U. 11 Several compounds produce the C−C coupled product catalytically, 6a,8,9c,12 with the most extensively studied system promoted by {Me 2 Si(C 5 Me 4 )(NPh)}Y(CH 2 SiMe 3 )(THF).…”
mentioning
confidence: 99%
“…Carbodiimide insertion into M–C bonds of terminal acetylides to afford the corresponding propargylamidinate has been documented for Li, K, Ca, Y, Sm, Yb, Lu, and U . Several compounds produce the C–C coupled product catalytically, ,,, with the most extensively studied system promoted by {Me 2 Si(C 5 Me 4 )(NPh)}Y(CH 2 SiMe 3 )(THF) .…”
mentioning
confidence: 99%